Renaming the Narrative, Reclaiming Their Humanity: Black and Latino Males' Descriptions of Success. Issue 5 (May 2019) - Howard, Tyrone C.; Woodward, Brian; Navarro, Oscar; Huerta, Adrian H.; Haro, Bianca N.; Watson, Kenjus
Background/Context: An ongoing challenge for scholars who examine the educational experiences of young men of color, particularly Black and Latino males, is to illustrate the complex nature of their experiences and to call into question the dichotomous narrative that these students are either successful or unsuccessful. There is a responsibility for scholars to present a balanced, more nuanced analysis and to highlight that, while a significant number of these young men are underperforming compared to their peers from other backgrounds, there are many students who are doing quite well in school. While interrogating the notion of success can be a complex task, one of the concerns in the professional literature has been that the definition is frequently limited to narrow or conventional standards (i.e., high GPA, high test scores, etc.). While these examples of success are indeed important, we maintain that they do not capture the full spectrum of favorable educational and social outcomes of Black and Latino male students both inside and outside of schools. Purpose/Objective: This study operates from the standpoint that many Black and Latino males are thriving, yet their stories are rarely told, especially by the young men themselves. The objective of the study is to challenge conventional depictions of Black and Latino males by better understanding how these young men perceive themselves, as well as how they conceptualize success. Thus, the questions that anchored this study include: How do Black and Latino males describe themselves? In what ways do they operationalize the term "success"? And what can researchers, practitioners, and policymakers learn from student perceptions of success? Research Design: The study included in-depth qualitative interviews that were conducted in person. The interviews were audio recorded and subsequently transcribed. Transcripts were uploaded to a qualitative data analysis program. Prevalent themes, topics, key terms, and phrases were all identified and ultimately represented recurring patterns and codes within the data. Findings/Results: Students defined success in similar ways to how they described themselves. "Hardworking, " "determined, " and "able to work with others" were a few descriptors offered by the participants. Moreover, the young men expressed an inherent belief that success was not relegated to school alone and that it was equally important to make their mark in their respective homes and communities. Establishing financial security, emphasizing self-improvement, helping their families and communities, and just wanting to be happy were other ways in which the participants defined success. Conclusion: Allowing students to develop their own definitions of success can serve as an impetus toward a shift away from thinking that success is in how others define the term. Success for these young men was the ability to write their own narrative.